The dilemmas that new teachers face in institutions of higher education. - Montenegro Obando, Blanca Liliana; Rodríguez Torres, Íngel Freddy (SATHIRI, 2019)
At present the changes that occur in society  influence the way students learn. The reforms to thecurrent regulations produced a generational change of academic staff in higher education institutions.Teachers are key in the educational process and responsible for generating favorable conditions forstudents to learn and be able to perform effectively in their profession. The new university faculty facesproblems related to teaching, management, interpersonal relationships, research and the relationship with society. This demands the need to maintain a personal and professional balance to offer a quality education. The objective of the study is to analyze the dilemmas faced by the new university teaching staff and their impact on their teaching performance. For this a systematic bibliographic review was carried out in order to document the problem, specific databases and repositories of scientific journals were consulted. It was evidenced that the new teachers demonstrate mastery in their area of knowledge, but most of them lack pedagogical training. Generating difficulties in the planning of teaching, using a variety of methodological strategies, evaluation of learning, class organization and classroom management impacting on their professional performance. Given this situation, it is necessary to reconstruct their professional identity and that higher education institutions have professional development plans so that the new teachers adapt to the new roles and functions they will develop in their teaching management.
Keywords: University teaching staff; novice teachers; university faculty competencies; higher education institutions; higher education